Macroporous Hydrogel Dressing: A Macroporous Hydrogel Dressing with Enhanced Antibacterial and Anti‐Inflammatory Capabilities for Accelerated Wound Healing (Adv. Funct. Mater. 21/2020). (20th May 2020) - Huang, Wen‐Can; Ying, Rui; Wang, Wei; Guo, Yuning; He, Yongjun; Mo, Xinya; Xue, Changhu; Mao, Xiangzhao
Abstract : In article number 2000644, Changhu Xue, Xiangzhao Mao, and co‐workers develop a macroporous hydrogel dressing with antibacterial and anti‐inflammatory properties for accelerated wound healing. The hydrogel matrix is formed by hydrogen bonding and supramolecular complexation. The hydrogel shows outstanding biocompatibility and can significantly accelerate skin tissue regeneration and wound closure.